Mapping a Magnetic Superstorm: March 1989 Geoelectric Hazards and Impacts on United States Power Systems - Jeffrey J. Love; Greg M. Lucas; E. Joshua Rigler; Benjamin S. Murphy; Anna Kelbert; Paul A. Bedrosian (Space Weather)
Abstract A study is made of the relations between geomagnetic and geoelectric field variation, Earth‐surface impedance, and operational interference (“anomalies”) experienced on electric‐power systems across the contiguous United States during the 13–14 March, 1989, magnetic storm. For this, a 1‐min‐resolution sequence of geomagnetic field maps is constructed from magnetometer time series acquired at ground‐based observatories. Induced geoelectric field maps are calculated by convolving the geomagnetic maps with magnetotelluric impedance tensors. During the storm, anomalies were concentrated where the lithosphere is electrically resistive, and when and where geoelectric field amplitudes were high. This was particularly true in the Mid‐Atlantic, Northeast, and the upper Midwest. Few anomalies were experienced in other parts of the Midwest and across much of the West, where the lithosphere is more conductive, and when and where geoelectric field amplitudes were low. Peak 1‐min‐resolution geoelectric field amplitude ranged from 21.66 V/km in Maine and 19.02 V/km in Virginia to <0.02 V/km in Idaho. Latitude‐dependent organization of geoelectric hazards by auroral‐zone electrojet currents is detectable, but it is much weaker than geographic organization due to surface impedance. Hazardous geoelectric fields were induced during different storm phases, at different local times, and, by inference, by a variety of ionospheric currents. Compared to geoelectric field amplitudes realized across the United States during March 1989, hazard maps used by utility companies to estimate systems exposure have much less geographic detail and a much smaller maximum‐to‐minimum range in geoelectric field amplitude. Future research would benefit from denser geomagnetic monitoring, additional magnetotelluric surveying, and access to power‐system impact data.